Finance and Development, September 1987. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1987)
The enhancement of the IMF's structural adjustment facility is discussed. In its April 1987 meeting, the IMF's Interim Committee highlighted the plight of low-income countries, and outlined a strategy for their recovery. It emphasized that it is crucial for these countries to implement reforms that to be fully effective, will need to be accompanied by the timely provision of additional financing on appropriate concessional terms to support these reforms. The Committee also called upon creditor governments to grant exceptional relief with respect to official credits in highly indebted low-income countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet